The Research of Slow Release Nitrogen Fertilizer Applied in Sugarcane (Saccharum officinarum) for Green Energy Bioethanol - Tri Atmodjo; Agus Eko T. Nurul Rusdi; Sigit Setiadi; . Rina (International Conference on Engineering and Technology Development (ICETD), 2013)
This Research was conducted in order to find out the influence of Slow Release Nitrogen Fertilizer and Nitrogen Fertilizer for sugarcane plant as the raw materials of green energy bioethanol  The  Sugarcane plant needs fertilizer in order to improve plant productivity.  The chemical fertilizer usually not circumctance friendly but the slow release chemical fertlilizer may have something  different.  The application of slow release chemical  fertilizer may be  better for soil fertility The application of slow release nitrogen fertilizer in GMP 2 and Kidang Kencana sugarcane plant  seemed better rather than ordinary nitogen fertilizer in Yellow – Red Podzolic Soil in Negara Bumi Ilir,  Center of Lampung.